Pengaruh Kualitas Layanan Logistik, Ketepatan Waktu dan Fasilitas Terhadap Kepuasan Pelanggan JNE Cikarang Selatan - Cecep Ramdani; Muhammad Kosim; Adibah Yahya (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of logistics service quality, on-time delivery, and facilities on JNE customer satisfaction in South Cikarang. The methodology used is a quantitative approach with data collection through questionnaires to 81 respondents, and data analysis using SEM (Structural Equation Modeling) techniques with the SmartPLS 3.0 application. The results of the study indicate that on-time delivery and facilities have a positive and significant effect on customer satisfaction, while the quality of logistics services does not have a significant effect. This study emphasizes the importance of on-time delivery and the provision of adequate facilities in increasing customer satisfaction levels. This study also shows that the development of information technology simplifies the service process and improves customer experience in logistics services.